2021
DOI: 10.3389/fpls.2021.779382
|View full text |Cite
|
Sign up to set email alerts
|

Melatonin Enhances Drought Tolerance by Regulating Leaf Stomatal Behavior, Carbon and Nitrogen Metabolism, and Related Gene Expression in Maize Plants

Abstract: It is commonly known that exogenously applied melatonin can alleviate the impact of drought stress, but the mechanism used by melatonin to regulate stomatal behavior and carbon (C) and nitrogen (N) metabolism to increase drought resistance remains elusive. Herein, our aim was to investigate the influence of exogenous melatonin on the regulation of C and N metabolism in maize plants under water deficit. In this study, we analyzed stomatal behavior, the key components of C and N metabolism, and the gene expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(17 citation statements)
references
References 86 publications
0
16
0
1
Order By: Relevance
“…Melatonin is a multifunctional regulator in plant response to drought stress. (1) The accumulation of osmolytes, such as free proline, were enhanced in melatonin-treated plants, significantly alleviating adverse effects by facilitating the maintenance of optimum turgor pressure ( Zhao et al, 2021 ). (2) Melatonin induces the expression of transcription factors and modulates the expression of downstream stress-responsive genes, thereby increasing plant drought tolerance ( Sharma and Zheng, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Melatonin is a multifunctional regulator in plant response to drought stress. (1) The accumulation of osmolytes, such as free proline, were enhanced in melatonin-treated plants, significantly alleviating adverse effects by facilitating the maintenance of optimum turgor pressure ( Zhao et al, 2021 ). (2) Melatonin induces the expression of transcription factors and modulates the expression of downstream stress-responsive genes, thereby increasing plant drought tolerance ( Sharma and Zheng, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Melatonin is a multifunctional regulator in plant response to drought stress. (1) The accumulation of osmolytes, such as free proline, were enhanced in melatonin-treated plants, significantly alleviating adverse effects by facilitating the maintenance of optimum turgor pressure (Zhao et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…Under drought stress, the GS activity in silty loam was significantly higher than in sandy clay, and the GS activity in sandy clay was significantly higher than in clay loam. Studies have shown that under short-term or mild water stress, GS and GOGAT activities increase in the short term to remove previously metabolically accumulated NH 4 + ) in order to weaken or eliminate the toxic effects of NH 4 + accumulation on plant cells (Zhao et al 2021). However, when the stress time was too long, or the stress degree was too heavy, the activities of GS and GOGAT decreased significantly due to the limitation of NR activity (Zhao et al 2021).…”
mentioning
confidence: 99%
“…Studies have shown that under short-term or mild water stress, GS and GOGAT activities increase in the short term to remove previously metabolically accumulated NH 4 + ) in order to weaken or eliminate the toxic effects of NH 4 + accumulation on plant cells (Zhao et al 2021). However, when the stress time was too long, or the stress degree was too heavy, the activities of GS and GOGAT decreased significantly due to the limitation of NR activity (Zhao et al 2021). It has also been suggested that the decrease in GS and GOGAT activity under severe drought or prolonged drought conditions is due to increased hydrolase activity (Cao et al 2022)…”
mentioning
confidence: 99%
See 1 more Smart Citation